KAJIAN PENERAPAN CARA PRODUKSI PANGAN OLAHAN YANG BAIK (CPPOB) PADA USAHA MIKRO KECIL (UMK) DIMSUM BAYAM (DIYAM) (JURNAL ILMIAH AGROINDUSTRI (JIA), 2025)
This research aims to understand the production process at UMK DIYAM, evaluate the level of CPPOB compliance, and provide improvement recommendations that can be implemented. The method used is descriptive with a qualitative approach, as well as GAP Analysis to measure the percentage of CPPOB compliance and Root Cause Analysis to identify the causes of non-compliance. The research results show that the production process at UMK DIYAM includes the stages of cleaning, washing, cutting, refining, dough making, dough forming, steaming, packaging, storage, and distribution. The level of CPPOB compliance was recorded as 48% fulfilled, 50% not fulfilled, and 2% not applicable. The recommendations provided include CPPOB training programs, installation of command or warning boards, preparation of duty schedules, and addition of facilities and personnel.